Hybrid equation-of-motion coupled-cluster/effective fragment potential method: a route toward understanding photoprocesses in the condensed phase - Ghosh, Debashree (Journal of Physical Chemistry A, 2017)
The prediction of accurate solvatochromic shifts to the electronic excited states of chromophores is a challenge, especially in the complex biological phase, due to the importance of long-range electrostatic interactions. Hybrid quantum mechanical/molecular mechanical (QM/MM) methods are generally employed for the calculation of quantum mechanical properties in complex systems. To be predictive, there is need for an accurate quantum mechanical method that can depict the charge transfer states correctly and incorporate higher than single excited determinants in its linear response ansatz. On the contrary, for the correct depiction of the environment interactions (MM region), one needs to account for polarizability in a balanced manner. These two challenges are successfully addressed by the recently developed hybrid quantum mechanical/effective fragment potential (QM/EFP) methods, with equation-of-motion coupled-cluster (EOM-CC) as the QM method of choice. The result is an efficient method to estimate excitation energy, ionization energy, electron affinity, and redox potential in the condensed phase. It has further been extended to biological systems.